Magnetic ground state of the one-dimensional ferromagnetic chain compounds M(NCS)(2)(thiourea)(2) (M = Ni, Co) - Curley, SPM; Scatena, R; Williams, RC; Goddard, PA; Macchi, P; Hicken, TJ; Lancaster, T; Xiao, F; Blundell, SJ; Zapf, V; Eckert, JC; Krenkel, EH; et al. (American Physical Society, 2021)
The magnetic properties of the two isostructural molecule-based magnets - Ni(NCS)2(thiourea)2, S=1 [thiourea=SC(NH2)2] and Co(NCS)2(thiourea)2, S=3/2 - are characterized using several techniques in order to rationalize their relationship with structural parameters and to ascertain magnetic changes caused by substitution of the spin. Zero-field heat capacity and muon-spin relaxation measurements reveal low-temperature long-range ordering in both compounds, in addition to Ising-like (D<0) single-ion anisotropy (DCo∼-100 K, DNi∼-10 K). Crystal and electronic structure, combined with dc-field magnetometry, affirm highly quasi-one-dimensional behavior, with ferromagnetic intrachain exchange interactions JCo≈+4 K and JNi∼+100 K and weak antiferromagnetic interchain exchange, on the order of J′∼-0.1 K. Electron charge- and spin-density mapping reveals through-space exchange as a mechanism to explain the large discrepancy in J-values despite, from a structural perspective, the highly similar exchange pathways in both materials. Both species can be compared to the similar compounds MCl2(thiourea)4, M = Ni(II) (DTN) and Co(II) (DTC), where DTN is known to harbor two magnetic-field-induced quantum critical points. Direct comparison of DTN and DTC with the compounds studied here shows that substituting the halide Cl- ion for the NCS- ion results in a dramatic change in both the structural and magnetic properties.